PENIGKATAN HASIL BELAJAR SISWA KELAS I SD PADA MATA PELAJARAN MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN MELALUI METODE JARIMATIKA - Mihra; Putri Rahmadani; Nurul Miranda Ansar; Muh Ilyas; Sulfasyah; Haris (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the learning outcomes of first-grade elementary school students using the jarimatika method. The type of research in this study is Classroom Action Research (CAR) which will be implemented in a minimum of two cycles, where there are 4 meetings in one cycle and there are two lesson hours in one meeting. The subjects in this study were first-grade students with a total of 12 male students and 16 female students. This research procedure uses the Kemmis and Mc Taggart model which consists of four stages of activities, namely planning, implementation, observation and reflection. Student learning outcomes from cycle I to cycle II have increased. In cycle I, the completeness of student learning achievement was 71.43% and in cycle II, the completeness of student learning outcomes increased to 92.86%. The application of the jarimatika method in the learning process can improve the Mathematic learning outcomes of first-grade elementary school students.